Self-Efficacy on Intradialysis Hypertension in Kidney Failure Patients - Rizkya Ayunarwanti; Arina Maliya (Jurnal Berita Ilmu Keperawatan, 2020)
Chronic kidney failure is a disorder of function in which the body fails to maintain metabolism, fluid balance, and electrolytes that require long-term therapy with hemodialysis therapy. Complications that occur during hemodialysis are hypertension, hypotension, muscle cramps, vomiting, and nausea. Self-efficacy is effective to improve treatment of patients with chronic kidney failure. One of the factors that influence success is self-efficacy. Method: literature review with several journals that have been conducted research on intradialysis hypertension and self efficacy in patients with chronic renal failure through Pubmed, Neliti, and Google Scholar searches with keywords self efficacy in intradialysis hypertension in the 2015-2020 period. Results: Intradialysis hypertension is one of the difficult factors for durante HD. Factors related to self efficacy and quality of life of patients who are approved Age, patients living with family, patients with comorbid diseases. Self-care training programs can increase self-efficacy in patients. Conclusion: Intradialysis hypertension based on the characteristics of age, sex, IDWG more than normal, length of hemodialysis, the amount of antihypertensive drugs consumed. Self-efficacy is divided into 2, namely high self-efficacy and low self-efficacy. High self-efficacy and a very good quality of life make patients neat and obedient to the treatment process. The inability of a patient to adjust to his illness is a decrease in quality of life.